Multi-Store Competition: Market Segmentation or Interlacing? - Maarten C.W. Janssen; Vladimir A. Karamychev; Peran van Reeven (Tinbergen Institute, 2003)
This paper develops a model for multi-store competition between firms. Using thefact that different firms have different outlets and produce horizontally differentiated goods, we obtain a pure strategy equilibrium where firms choose a different location for each outlet and firms' locations are interlaced. Moreover, generically, the subgame perfect equilibrium isunique and when the firms have an equal number of outlets, prices are independent of the number of outlets.
Keywords: I18; D10; Z13; 330; multi-store competition; hotelling; interlacing; Einzelhandel; Filiale; Marktsegmentierung; Hotelling-Modell